2022
DOI: 10.1155/2022/4599305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Associated with Cancerous Change in Oral Leukoplakia Based on Integrated Transcriptome Analysis

Abstract: Objective. Oral leukoplakia (OLK) is the most common precancerous lesion in the oral cavity. This study aimed to explore key biomarkers for monitoring OLK for early diagnosis of oral squamous cell carcinoma (OSCC) and screen small-molecule drugs for the prevention of OSCC. Method. The Gene Expression Omnibus (GEO) database was explored to extract two microarray datasets, namely, GSE85195 and GSE25099. The data of the normal group, OLK group, and OSCC group were analyzed by weighted gene coexpression network an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Though the impacts of hyperglycemia on individuals' pro-inflammatory cytokine and MMP secretions have been reported [12,14,22,23], our multi-omics integration model highlighted new relationships between genes, pro-inflammatory cytokines and bacteria genera implicated in periodontitis-induced inflammatory response in a hyperglycemic microenvironment. Highlighted genes have been associated with DNA damage response (znf506) [24], cancer (pnma5) [25] and oral cancer (krt76, rab41) [26][27][28]. We have also identified tm6sf2, which is associated with both the risk and the severity of nonalcoholic fatty liver disease [29] as well as with the regulation of inflammatory responses in atherosclerotic lesions [30].…”
Section: Discussionmentioning
confidence: 93%
“…Though the impacts of hyperglycemia on individuals' pro-inflammatory cytokine and MMP secretions have been reported [12,14,22,23], our multi-omics integration model highlighted new relationships between genes, pro-inflammatory cytokines and bacteria genera implicated in periodontitis-induced inflammatory response in a hyperglycemic microenvironment. Highlighted genes have been associated with DNA damage response (znf506) [24], cancer (pnma5) [25] and oral cancer (krt76, rab41) [26][27][28]. We have also identified tm6sf2, which is associated with both the risk and the severity of nonalcoholic fatty liver disease [29] as well as with the regulation of inflammatory responses in atherosclerotic lesions [30].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, associations between NKX2‐3 and prognosis have been reported (Zhu et al, 2020) and Abe et al (2016) described that oral leucoplakias are associated with aberrant promoter methylation of NKX2‐3 . Importantly, KRT3 was also selected as a potential diagnostic biomarker associated with a cancerous change in oral leukoplakia (Li et al, 2022). Lin et al (2016) reported that BARX2 expression is mostly downregulated in OSCC and that its expression suppresses the expansion of OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP3A4 gene encodes a member of the cytochrome P450 superfamily of enzymes and is involved in the metabolism of sterols, steroid hormones, retinoids, and fatty acids ( Chen et al., 2000 ; Marill et al., 2000 ; Badawi et al., 2001 ). Cytoscape software by the Matthews correlation coefficient (MCC) algorithm was used to predict CYP3A4 at the core position in the network and highlight the first 10 types of OSCC DEGs ( Li et al., 2022 ). It is worth noting that there found 350 homologous proteins including 45 microbes were found by evolutionary analysis in this study.…”
Section: Discussionmentioning
confidence: 99%